Pelatihan Desain dan Pemodelan Bangunan Rumah 2 Lantai Menggunakan Program SAP 2000 di Jurusan Desain Pemodelan Informasi Bangunan (DPIB) SMK PGRI 1 Gresik - hidayat dayat (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
In an effort to maintain the quality of education on the influence of the development of information technology contained in the SMK curriculum majoring in Building Information Modeling Design in building structure subjects, it is necessary to introduce to students that there is a computer program that can support it. The computer program is SAP 2000 which can be used to analyze the forces acting on the structure of beams, columns, plates, and the cross-section of a 2-story house construction. As a form of effort that can be made to maintain the quality of education on the influence of the development of information technology contained in the SMK curriculum, majoring in Building Information Modeling Design (DPIB) in building structure subjects, it is necessary to make a proposal to hold an activity